DEVELOPMENT SYSTEM FOR SOLVING TWO-DIMENSIONAL AND THREE-DIMENSIONAL ELASTICITY THEORY PROBLEMS BASED ON MAPLE - Ovskiy, A. G.; Tolok, V. A. (Radio Electronics, Computer Science, Control, 2011)
Анотація